Characterization of a lipase in Arabidopsis defense - Morton, Jessica (Kansas State University, 2007)
Plant defense responses are constitutively activated in the Arabidopsis thaliana ssi2 mutant plant. In addition, the ssi2 mutant allele confers a dwarf phenotype. The SSI2 gene encodes a stearoyl-ACP-desaturase, which converts stearic acid (18:0) to oleic acid (18:1), suggesting a role for lipids in plant defense. Microarray analysis identified several genes which encode putative acyl hydrolases/lipases that are expressed at elevated levels in the leaves of ssi2, in comparison to the wild type plant. One gene in particular, At5g14180, was expressed at 60-fold greater level in ssi2 than in the wild type plant. To study the involvement of At5g14180 in plant defense and lipid metabolism, two transgenic lines containing T-DNA insertions within the At5g14180 gene were identified. These two T-DNA insertional alleles of the At5g14180 gene attenuate the ssi2-conferred heightened resistance to a virulent strain of Pseudomonas syringae pv. maculicola in the ssi2 At5g14180 double mutant plant. Furthermore, pathogen growth was enhanced in the At5g14180 single mutant plants, as compared to the wild type plant. Profiling of lipid composition in leaf tissue identified changes in the lipid composition between the At5g14180 mutant and wild type plants, suggesting that the At5g14180 encoded protein may impact lipid metabolism in Arabidopsis leaves.
Keywords: Arabidopsis; Defense; Biology, Genetics (0369); Biology, Molecular (0307); Biology, Plant Physiology (0817)